Rivals - Greenwald, Tom, 1962- (Amulet Books, 2021)
In basketball-crazed Walthorne, rival middle school stars Austin Chambers and Carter Haswell are both feeling the pressure when school sports reporter Alfie Jenks reveals scandals that jeopardize the whole season. Told through flashbacks, newspaper reports, social media posts, and interviews.